Web 2.0 - Solomon, Gwen (International Society for Technology in Education, 2007)
Includes bibliographical references (pages 235-250) and index.; New world, new web, new skills -- Students and learning -- New tools -- New tools in schools -- Professional development -- Leadership and new tools -- Online safety and security -- Systemic issues -- New schools -- Tutorials.; Provides an overview of the emerging Web 2.0 technologies and their use in the classroom and in professional development.; Remote access restricted to American University authorized users.